Lithium-ion secondary battery and electric device

CN122968239APending Publication Date: 2026-10-23CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510517603.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-23
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

而传统的锂离子二次电池能量密度、循环寿命以及充电性能的兼顾性有待进一步提高

Benefits of technology

[0009]在一些实施方式中,所述石墨的平均粒径为6μm~12μm。平均粒径大于或等于6μm的石墨在生产上易于制备,可以降低石墨以及锂离子二次电池的制造成本。平均粒径小于或等于12μm的石墨在被硅碳复合材料挤压时出现变形的程度较低,在电池的充放电过程中可以保持较为稳定的结构,进而可以进一步提高锂离子二次电池的循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968239A_ABST
    Figure CN122968239A_ABST
Patent Text Reader

Abstract

The application provides a lithium ion secondary battery and a power utilization device. The lithium ion secondary battery comprises a negative electrode sheet, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer on at least one surface of the negative electrode current collector, and a negative electrode active material of the negative electrode active layer comprises a silicon-carbon composite material and graphite, the average particle size of the silicon-carbon composite material is less than or equal to 10 mu m, and the ratio of the average particle size of the silicon-carbon composite material to the average particle size of the graphite is 0.8-1.2. The lithium ion secondary battery can balance good cycle life and fast charging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a lithium-ion secondary battery and an electrical device. Background Technology

[0002] In recent years, lithium-ion rechargeable batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and many other fields. With the continuous expansion of the application scope of lithium-ion rechargeable batteries, correspondingly higher requirements are being placed on battery performance.

[0003] For example, energy density, cycle life, and charging performance are important indicators for evaluating the performance of lithium-ion rechargeable batteries. However, the balance between energy density, cycle life, and charging performance in traditional lithium-ion rechargeable batteries needs further improvement. Summary of the Invention

[0004] The first aspect of this application provides a lithium-ion secondary battery, including a negative electrode sheet, the negative electrode sheet including a negative current collector and a negative active layer located on at least one surface of the negative current collector, the negative active material of the negative active layer including a silicon-carbon composite material and graphite, the average particle size of the silicon-carbon composite material being less than or equal to 10 μm, and the ratio of the average particle size of the silicon-carbon composite material to the average particle size of the graphite being 0.8 to 1.2; the silicon-carbon composite material including a porous carbon substrate having a porous structure, the porous carbon substrate having silicon-containing materials distributed within the porous structure.

[0005] In lithium-ion rechargeable batteries, the introduction of silicon-based anode active materials can improve the battery's energy density. However, the volume change of silicon-based anode active materials during battery charging and discharging is greater than that of graphite. This leads to disruption of the particle arrangement between the silicon-based anode active material and graphite, resulting in reduced uniformity of pore distribution within the anode active layer, and consequently deteriorating the battery's cycle performance and fast-charging performance. This application introduces silicon-carbon composite materials into lithium-ion rechargeable batteries, using a porous carbon structure with silicon distributed within it to reduce the expansion of the silicon-based anode active material. However, compared to other silicon-based anode active materials, such as silicon-oxygen materials, silicon-carbon composite materials have irregular morphology and greater hardness than graphite. When used in combination with graphite as a composite anode active material, it easily damages and deforms graphite particles, increasing the defects in the graphite itself, while simultaneously worsening the uniformity of pore distribution in the anode active layer, increasing active lithium loss and polarization loss, and deteriorating cycle performance and fast-charging performance.

[0006] The inventors discovered that in lithium-ion secondary batteries, using silicon-carbon composite materials with smaller average particle sizes results in less volume change during battery charging and discharging, potentially reducing the impact of silicon-carbon composite material volume changes on the uniformity of pore distribution within the negative electrode active layer. However, if the average particle sizes of the silicon-carbon composite material and graphite differ significantly, it can still disrupt the uniformity of pore distribution within the negative electrode active layer. For example, when the average particle size of the silicon-carbon composite material is significantly smaller than that of graphite, the expansion of the smaller silicon-carbon composite material causes significant rotation of the graphite, disrupting the uniformity of pore distribution within the negative electrode active layer. Conversely, when the average particle size of the silicon-carbon composite material is significantly larger than that of graphite, the volume expansion of the silicon-carbon composite material occupies a large amount of pores, significantly compressing the space of the graphite and disrupting the uniformity of pore distribution within the negative electrode active layer. Based on this, this application selects a silicon-carbon composite material with a smaller average particle size. At the same time, the ratio of the average particle size of the silicon-carbon composite material to the average particle size of graphite is 0.8 to 1.2. Since the particle sizes of the two are similar, the influence of the charging and discharging process of the battery on the particle arrangement between the silicon-carbon composite material and graphite can be reduced, so that the negative electrode active layer maintains a relatively uniform pore distribution. In this way, the battery containing silicon-based negative electrode active material can achieve both good cycle life and fast charging performance.

[0007] In some embodiments, the silicon-carbon composite material and the graphite are mixed together. Mixing the silicon-carbon composite material and graphite can make the porosity distribution within the negative electrode active layer more uniform, further improving the cycle life of the lithium-ion secondary battery.

[0008] In some embodiments, the average particle size of the silicon-carbon composite material is greater than or equal to 7 μm.

[0009] In some embodiments, the average particle size of the graphite is 6 μm to 12 μm. Graphite with an average particle size greater than or equal to 6 μm is easy to produce, which can reduce the manufacturing cost of graphite and lithium-ion secondary batteries. Graphite with an average particle size less than or equal to 12 μm exhibits less deformation when extruded by silicon-carbon composite materials, and can maintain a more stable structure during battery charging and discharging, thereby further improving the cycle life of lithium-ion secondary batteries.

[0010] In some embodiments, the sphericity of the graphite is 0.5 to 1. A higher sphericity results in a more regular shape, reducing the risk of deformation under compression. Therefore, graphite within this sphericity range maintains good structural stability under compression, further improving the cycle life of lithium-ion secondary batteries.

[0011] In some embodiments, the graphite comprises monocrystalline artificial graphite. Monocrystalline artificial graphite has a more regular crystal structure with fewer crystal defects. When compressed, monocrystalline artificial graphite can maintain a more stable structure, thereby further improving the cycle life of lithium-ion secondary batteries.

[0012] In some embodiments, the compacted density of the graphite powder under a pressure of 30,000 N is 1.6 g / cm³. 3 ~1.8g / cm 3 The compacted density of graphite powder is greater than or equal to 1.6 g / cm³. 3 This allows the negative electrode active layer to have a high compaction density, thereby improving the energy density of lithium-ion secondary batteries. The compaction density of graphite powder is less than or equal to 1.8 g / cm³. 3 This helps to ensure that the negative electrode active layer has a suitable porosity, promotes lithium-ion transport, and further improves the cycle life of lithium-ion secondary batteries.

[0013] In some embodiments, the tap density of the graphite is 1.05 g / cm³. 3 ~1.25g / cm 3 Graphite with a tap density within this range can maintain a relatively stable structure during battery charging and discharging, and can better withstand the volume changes caused by lithium-ion insertion and extraction, further improving the cycle life of lithium-ion secondary batteries.

[0014] In some embodiments, the sphericity of the silicon-carbon composite material is 0.5 to 1. The relatively high sphericity and regular shape of the silicon-carbon composite material can reduce stress concentration in the negative electrode active layer during volume changes, lower the risk of cracks and breakage in the negative electrode active material, and further improve the cycle life of the lithium-ion secondary battery.

[0015] In some embodiments, the silicon-carbon composite material has a powder compaction density of 0.9 g / cm³ under a pressure of 30,000 N. 3 ~1.2g / cm 3 Within this range, the compacted density of silicon-carbon composite powder allows lithium-ion secondary batteries to better balance improved energy density and cycle life.

[0016] In some embodiments, the tap density of the silicon-carbon composite material is 0.9 g / cm³. 3 ~1.1g / cm 3 The tap density of silicon-carbon composite materials within this range is beneficial for maintaining a relatively stable structure of the negative electrode active layer during battery charging and discharging, thereby improving the battery's cycle life while increasing its energy density.

[0017] In some embodiments, the silicon-containing material includes elemental silicon and lithium silicate located on the surface of the elemental silicon.

[0018] In some embodiments, the silicon-carbon composite material accounts for 1% to 50% of the mass percentage of the negative electrode active material. When the mass percentage of the silicon-carbon composite material in the negative electrode active material is greater than or equal to 1%, the high specific capacity of the silicon-carbon composite material can be utilized to promote the improvement of the energy density of the lithium-ion secondary battery. When the mass percentage of the silicon-carbon composite material in the negative electrode active material is less than or equal to 50%, the volume change of the negative electrode active layer during battery charging and discharging can be controlled within a suitable range, which is beneficial to improving the cycle life of the lithium-ion secondary battery. Optionally, the silicon-carbon composite material accounts for 5% to 30% of the mass percentage of the negative electrode active material.

[0019] In some embodiments, the silicon-carbon composite material accounts for 0.9% to 49% of the mass percentage of the negative electrode active layer.

[0020] In some embodiments, the graphite constitutes 50% to 99% of the mass of the negative electrode active material. This range of graphite mass percentage in the negative electrode active material allows for a better balance between energy density and cycle life in the lithium-ion secondary battery. Optionally, the graphite constitutes 70% to 95% of the mass of the negative electrode active material.

[0021] In some embodiments, the compacted density of the negative electrode active material at a pressure of 30,000 N is 1.25 g / cm³. 3 ~1.8g / cm 3 .

[0022] In some embodiments, the tap density of the negative electrode active material is 0.95 g / cm³. 3 ~1.25g / cm 3 .

[0023] In some embodiments, the compaction density of the negative electrode active layer is 1.4 g / cm³. 3 ~1.65g / cm 3 The compaction density of the negative electrode active layer is greater than or equal to 1.4 g / cm³. 3 This allows the battery to achieve a higher energy density while maintaining good contact between the negative electrode active materials, which is beneficial for improving the battery's kinetic performance and further enhancing its cycle life. Additionally, the compaction density of the negative electrode active layer is less than or equal to 1.65 g / cm³. 3 The electrolyte can more fully wet the negative electrode active layer, enabling lithium ions to be transported more efficiently in the negative electrode active layer, which is beneficial to improving the battery cycle life.

[0024] A second aspect of this application provides an electrical device. The electrical device includes the lithium-ion secondary battery described in the first aspect. Attached Figure Description

[0025] To better describe and illustrate the embodiments or examples provided in this application, reference may be made to one or more accompanying drawings. Additional details or examples used to describe the drawings should not be considered as limiting the scope of any of the disclosed applications, the currently described embodiments or examples, or the best mode of conduct of these applications as currently understood. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings:

[0026] Figure 1 This is a schematic diagram of a lithium-ion secondary battery according to one embodiment of this application.

[0027] Figure 2 for Figure 1 An exploded view of a lithium-ion secondary battery according to an embodiment of this application is shown.

[0028] Figure 3 This is a schematic diagram of an electrical device that uses a lithium-ion secondary battery as a power source according to an embodiment of this application.

[0029] Figure 4 This is a cross-sectional morphology diagram of the negative electrode sheet of the lithium-ion secondary battery corresponding to Example 2 and Comparative Example 1 of this application.

[0030] Figure 5 The cross-section of the negative electrode sheet of the lithium-ion secondary battery corresponding to Example 2 and Comparative Example 1 of this application is analyzed using Avizo software.

[0031] Figure 6 This is a comparison chart of the charging rates of the lithium-ion secondary batteries corresponding to Example 2 and Comparative Example 1 of this application.

[0032] Explanation of reference numerals in the attached figures:

[0033] 1. Lithium-ion secondary battery; 11. Casing; 12. Electrode assembly; 13. Cover plate; 2. Electrical device. Detailed Implementation

[0034] To facilitate understanding of this application, a more complete description will be provided below with reference to the accompanying drawings. Preferred embodiments of this application are shown in the drawings. However, this application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of this application.

[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0036] The "range" disclosed in this application can be defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints. Any endpoint can be independently included or excluded, and they can be combined arbitrarily; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for a specific parameter, it is expected that ranges of 60~110 and 80~120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are also listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this application, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0" and "5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥2, it is equivalent to listing integers such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For instance, when a parameter is described as an integer selected from "2~10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9, and 10.

[0037] In this application, the terms "multiple" or "various" are used unless otherwise specified, referring to a quantity greater than or equal to 2. For example, "one or more" means one or more types.

[0038] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0039] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. The term "implementation" as used herein has a similar understanding.

[0040] Those skilled in the art will understand that the order in which the steps are written in the methods of various embodiments or examples does not imply a strict execution order and does not constitute any limitation on the implementation process. The detailed execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps of this application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0041] In this application, unless otherwise stated, “A, such as B” means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0042] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it means that it is selected from either "with" or "without." If there are multiple "optional" entries in a technical solution, unless otherwise specified and there are no contradictions or mutual constraints, each "optional" entry shall be independent.

[0043] In this application, unless otherwise specified, "lithium-ion secondary battery" refers to a basic unit capable of converting chemical energy into electrical energy, and more generally includes a positive electrode, a negative electrode, and an electrolyte. During the charging and discharging process of the battery, lithium ions repeatedly insert and extract between the positive and negative electrode.

[0044] The introduction of silicon-based anode active materials can improve the energy density of batteries. However, the volume change of silicon-based anode active materials during battery charging and discharging is greater than that of graphite. This leads to disruption of the particle arrangement between silicon-based anode active materials and graphite, resulting in reduced uniformity of pore distribution within the anode active layer, and consequently deteriorating the battery's cycle performance and fast-charging performance. Introducing silicon-carbon composite materials into lithium-ion secondary batteries can reduce the expansion of silicon-based anode active materials through a porous carbon structure with silicon distributed within it. However, compared to other silicon-based anode active materials, such as silicon-oxygen materials, silicon-carbon composite materials have irregular morphology and are harder than graphite. When used in combination with graphite as a composite anode active material, they easily damage and deform graphite particles, increasing the defects in the graphite itself, while simultaneously worsening the uniformity of pore distribution in the anode active layer, increasing active lithium loss and polarization loss, and deteriorating cycle performance and fast-charging performance.

[0045] One embodiment of this application provides a lithium-ion secondary battery. The lithium-ion secondary battery includes a negative electrode sheet, which includes a negative current collector and a negative active layer located on at least one surface of the negative current collector. The negative active material of the negative active layer includes a silicon-carbon composite material and graphite. The average particle size of the silicon-carbon composite material is less than or equal to 10 μm, and the ratio of the average particle size of the silicon-carbon composite material to the average particle size of the graphite is 0.8 to 1.2. The silicon-carbon composite material includes a porous carbon substrate, which has a porous structure in which silicon-containing materials are distributed.

[0046] During their research on lithium-ion secondary batteries, the inventors discovered that using silicon-carbon composite materials with smaller average particle sizes results in less volume change during battery charging and discharging, potentially reducing the impact of silicon-carbon composite material volume changes on the uniformity of pore distribution within the negative electrode active layer. However, if the average particle sizes of the silicon-carbon composite material and graphite differ significantly, it can still disrupt the uniformity of pore distribution within the negative electrode active layer. For example, when the average particle size of the silicon-carbon composite material is significantly smaller than that of graphite, the expansion of the smaller silicon-carbon composite material causes significant rotation of the graphite, disrupting the uniformity of pore distribution within the negative electrode active layer. Conversely, when the average particle size of the silicon-carbon composite material is significantly larger than that of graphite, the volume expansion of the silicon-carbon composite material occupies a large amount of pores, significantly compressing the space of the graphite and disrupting the uniformity of pore distribution within the negative electrode active layer. Based on this, in the above embodiments, a silicon-carbon composite material with a small average particle size is selected. At the same time, the ratio of the average particle size of the silicon-carbon composite material to the average particle size of graphite is 0.8 to 1.2. Since the particle sizes of the two are similar, the influence of the battery charging and discharging process on the particle arrangement between the silicon-carbon composite material and graphite can be reduced, so that the negative electrode active layer maintains a relatively uniform pore distribution. In this way, the battery containing silicon-based negative electrode active material can achieve both good cycle life and fast charging performance.

[0047] For example, during battery charging and discharging, a uniform pore distribution within the negative electrode active layer allows for more stable lithium-ion transport efficiency, thereby improving the battery's cycle life. Furthermore, a uniform pore distribution within the negative electrode active layer during charging and discharging results in a more even distribution of stress, reducing the risk of stress concentration and thus minimizing the risk of structural damage such as cracks and breakage. This helps maintain the structural stability of the negative electrode active layer, further extending the battery's cycle life.

[0048] Furthermore, during battery charging and discharging, when the porosity distribution within the negative electrode active layer is uneven, with some areas having more pores and others fewer, the transport rate of lithium ions in different regions of the negative electrode active layer varies significantly. This leads to the problem of point-like lithium plating in lithium-ion secondary batteries during charging. In the lithium-ion secondary battery of this embodiment, however, the porosity distribution within the negative electrode active layer is uniform during charging and discharging, resulting in better uniformity of lithium ion transport in different regions of the negative electrode active layer. This reduces the risk of lithium plating during charging and thus promotes improved fast-charging performance.

[0049] Furthermore, the average particle size of the silicon-carbon composite material is relatively small, and the ratio of the average particle size of the silicon-carbon composite material to the average particle size of graphite is 0.8~1.2. At this time, the graphite also has a relatively small average particle size. During the charging and discharging process of the battery, the degree of deformation caused by the smaller average particle size of the graphite is reduced. This allows the graphite to maintain a relatively stable structure, which is beneficial to further improve the cycle life of lithium-ion secondary batteries.

[0050] In this application, the average particle size of the silicon-carbon composite material refers to the average particle size of the silicon-carbon composite material under full discharge conditions of the lithium-ion secondary battery. The average particle size of the graphite refers to the average particle size of the graphite under full discharge conditions of the lithium-ion secondary battery.

[0051] In this application, the average particle size of silicon-carbon composite material and graphite can be tested as follows: The lithium-ion secondary battery is fully discharged, disassembled, and the negative electrode sheet is removed. A 6mm × 6mm sample is cut from the negative electrode sheet. The sample is attached to an ion polisher and cut at 7.5kV for 30 minutes, perpendicular to the large surface of the electrode sheet. According to the JY / T010-1996 testing standard, the sample is tested and observed using a Sigma300 scanning electron microscope with energy dispersive spectroscopy. In backscatter mode, the bright particles are silicon-carbon composite material, and the black particles are graphite. By statistically analyzing the particle size within the region, the average particle size of the silicon-carbon composite material and graphite can be obtained. Simultaneously, the scanning images and Avizo software can be used to analyze the porosity differences in the negative electrode sheet.

[0052] Silicon-carbon composite materials with smaller average particle size have a larger specific surface area, providing more sites for lithium-ion insertion and extraction. This results in a more uniform reaction and mitigates volume changes caused by localized stress concentration during the reaction. Simultaneously, the smaller particle size of the silicon-carbon composite material itself results in smaller volume changes during charge and discharge. Using silicon-carbon composite materials with smaller average particle size in lithium-ion secondary batteries can reduce the volume change of the negative electrode during charge and discharge, thus improving battery cycle life. Optionally, the average particle size of the silicon-carbon composite material is 7μm to 10μm. For example, the average particle size of the silicon-carbon composite material can be 7μm, 7.2μm, 7.5μm, 7.8μm, 8μm, 8.2μm, 8.5μm, 8.8μm, 9μm, 9.2μm, 9.5μm, 9.8μm, 10μm, or any value within the range of any two of the above values.

[0053] The ratio of the average particle size of the silicon-carbon composite material to the average particle size of graphite is 0.8 to 1.2. Combined with the silicon-carbon composite material having a smaller average particle size, this results in a more uniform distribution of both materials, improving the uniformity of the pore distribution within the negative electrode active layer and thus enhancing the cycle life of the lithium-ion secondary battery. Optionally, the ratio of the average particle size of the silicon-carbon composite material to the average particle size of graphite can be 0.8, 0.82, 0.85, 0.88, 0.9, 0.92, 0.95, 0.98, 1, 1.02, 1.05, 1.08, 1.1, 1.12, 1.15, 1.18, 1.2, or any value within the range of any two of the above values.

[0054] In some embodiments, silicon-carbon composite materials and graphite are mixed together. The ratio of the average particle size of the silicon-carbon composite material to the average particle size of the graphite is 0.8 to 1.2. Combined with the silicon-carbon composite material with a smaller average particle size, the mixing of silicon-carbon composite material and graphite can make the porosity distribution inside the negative electrode active layer more uniform, thereby further improving the cycle life of the lithium-ion secondary battery.

[0055] Furthermore, the silicon-carbon composite material includes a porous carbon substrate with a pore structure containing silicon-containing materials. In this composite material, the porous carbon substrate provides numerous adhesion sites for the silicon-containing materials, buffering their expansion and resulting in a lower expansion rate. This reduces volume changes in the negative electrode during battery charging and discharging, improving cycle life and enabling lithium-ion rechargeable batteries to better balance higher energy density and better cycle life.

[0056] Optionally, the porous carbon substrate includes porous hard carbon. Porous hard carbon can provide better support for the expansion of silicon-containing materials, thereby reducing the overall expansion rate of the silicon-carbon composite material and further reducing the volume change of the negative electrode sheet during battery charging and discharging. In addition, porous hard carbon can maintain good particle integrity during the cycling process of lithium-ion secondary batteries, with a low risk of breakage and pulverization, which is beneficial to further improving the cycle life of lithium-ion secondary batteries.

[0057] In some embodiments, the silicon-containing material includes elemental silicon and lithium silicate located on the surface of the elemental silicon. Optionally, the elemental silicon includes nano-elemental silicon. Further optionally, the grain size of the nano-elemental silicon is less than or equal to 5.5 nm.

[0058] In some embodiments, the silicon-carbon composite material can be prepared by heating a porous carbon substrate to 500°C in a rotary kiln reactor under an argon atmosphere and holding it at that temperature for 0.5 to 1 hour to desorb the air adsorbed within the porous carbon substrate. Then, at 500°C, a mixture of silane and argon is introduced into the reactor at a flow rate of 4 L / min, wherein the volume ratio of silane to argon is 1:4. The silane decomposes, and silicon atoms are deposited in the pores of the porous carbon substrate to obtain the silicon-carbon composite material. In some embodiments, the first-cycle delithiation capacity of the prepared silicon-carbon composite material is 1400 mAh / g to 2300 mAh / g.

[0059] It is understandable that the silicon-carbon composite material prepared by the above method contains elemental silicon in the porous carbon substrate. When this silicon-carbon composite material is used in a battery, lithium ions react with the surface of elemental silicon to form lithium silicate during battery formation or cycling, thus yielding a silicon-containing material including elemental silicon and lithium silicate located on the surface of elemental silicon.

[0060] In some embodiments, the silicon-carbon composite material accounts for 1% to 50% of the mass percentage of the negative electrode active material. When the mass percentage of the silicon-carbon composite material in the negative electrode active material is greater than or equal to 1%, the high specific capacity of the silicon-carbon composite material can be utilized, promoting an increase in the energy density of the lithium-ion secondary battery. When the mass percentage of the silicon-carbon composite material in the negative electrode active material is less than or equal to 50%, the volume change of the negative electrode active layer during battery charging and discharging can be controlled within a suitable range, which is beneficial for improving the cycle life of the lithium-ion secondary battery. Optionally, the mass percentage of the silicon-carbon composite material in the negative electrode active material can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, or any value within the range of any two of the above values. Further optionally, the mass percentage of the silicon-carbon composite material in the negative electrode active material is 5% to 30%.

[0061] In some embodiments, the silicon-carbon composite material accounts for 0.9% to 49% of the mass percentage of the negative electrode active layer. Optionally, the mass percentage of the silicon-carbon composite material in the negative electrode active layer can be 0.9%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 49%, or any value within the range of any two of the above values.

[0062] In some embodiments, the average particle size of the graphite is 6 μm to 12 μm. Graphite with an average particle size greater than or equal to 6 μm is easy to produce, which can reduce the manufacturing cost of graphite and lithium-ion secondary batteries. Graphite with an average particle size less than or equal to 12 μm exhibits less deformation when extruded by silicon-carbon composite materials, and can maintain a more stable structure during battery charge and discharge, thereby further improving the cycle life of lithium-ion secondary batteries. Optionally, the average particle size of the graphite can be 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, or any value within the range of any two of the above values. More preferably, the average particle size of the graphite is 6 μm to 11 μm.

[0063] In some embodiments, the sphericity of the graphite is 0.5 to 1. At this value, the graphite has a relatively large sphericity, resulting in a more regular shape and a lower risk of deformation under compression. Therefore, graphite within this sphericity range can maintain good structural stability under compression, further improving the cycle life of lithium-ion secondary batteries. Optionally, the sphericity of the graphite can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, or any value within the range of any two of the above values.

[0064] It is understood that in this application, sphericity represents the ratio of the shortest diameter to the longest diameter of the material. It can be tested using the following method: ≥20 dispersed particles are image-captured and processed using a Malvern automated image particle size analyzer. Then, image-guided Raman spectroscopy (MDRS) is used to accurately analyze the microstructure and morphology of the particles, obtaining the longest and shortest diameters of all particles. The ratio of the shortest to the longest diameter of each particle is calculated to obtain the sphericity of each particle. The average sphericity of all particles is then taken as the sphericity.

[0065] In some embodiments, the graphite includes monolithic synthetic graphite. Monolithic synthetic graphite has a more regular crystal structure with fewer crystal defects. When compressed, monolithic synthetic graphite can maintain a more stable structure, thereby further improving the cycle life of lithium-ion secondary batteries.

[0066] In some embodiments, the compacted density of graphite powder under a pressure of 30,000 N is 1.6 g / cm³. 3 ~1.8g / cm 3 The compacted density of graphite powder is greater than or equal to 1.6 g / cm³. 3 This allows the negative electrode active layer to have a high compaction density, thereby improving the energy density of lithium-ion secondary batteries. The compaction density of graphite powder is less than or equal to 1.8 g / cm³. 3 This helps to ensure that the negative electrode active layer has a suitable porosity, promotes lithium-ion transport, and further improves the cycle life of lithium-ion secondary batteries. Optionally, the powder compaction density of graphite under 30000N pressure can be 1.6 g / cm³. 3 1.62g / cm 3 1.65g / cm 3 1.68g / cm 3 1.7g / cm 3 1.72g / cm 3 1.75g / cm 3 1.78g / cm 3 1.8g / cm 3And any value within the range consisting of any two of the above values.

[0067] In this application, the powder compaction density of the material has a well-known meaning in the art and can be tested using methods known in the art. For example, it can be tested using an electronic pressure testing machine, referring to GB / T 24533-2009: Place the powder sample to be tested with mass G on a special compaction mold with a bottom area S, set the pressure to 30000N, hold the pressure for 20s, release the pressure, wait for 10s, and read the thickness H of the powder after compaction under this pressure on the equipment. The powder compaction density under this pressure can be calculated as G / (H*S).

[0068] In some embodiments, the tap density of graphite is 1.05 g / cm³. 3 ~1.25g / cm 3 Graphite with a tap density within this range maintains a relatively stable structure during battery charging and discharging, and can better withstand the volume changes caused by lithium-ion insertion and extraction, further improving the cycle life of lithium-ion rechargeable batteries. Optionally, the tap density of graphite can be 1.05 g / cm³. 3 1.08g / cm 3 1.1g / cm 3 1.12 g / cm 3 1.15g / cm 3 1.18 g / cm 3 1.2g / cm 3 1.22g / cm 3 1.25g / cm 3 And any value within the range consisting of any two of the above values.

[0069] In this application, the tap density of the material can be tested using methods known in the art. For example, it can be determined using a powder tap density tester in accordance with standard GB / T 5162-2006. If a BT-312 tap density tester is used, the test parameters are as follows: vibration frequency 250±15 times / minute, amplitude 3±0.1mm, number of vibrations 5000 times, and measuring cylinder 25mL.

[0070] In some embodiments, graphite constitutes 50% to 99% of the mass percentage of the negative electrode active material. This range of graphite mass percentage in the negative electrode active material allows for a better balance between energy density and cycle life in the lithium-ion secondary battery. Optionally, the mass percentage of graphite in the negative electrode active material can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 99%, or any value within the range of any two of the above values. More preferably, the mass percentage of graphite in the negative electrode active material is 70% to 95%.

[0071] In some embodiments, the graphite constitutes 45% to 97% of the negative electrode active layer by mass. Optionally, the graphite constitutes 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 97%, or any value within the range of any two of the above values.

[0072] In some embodiments, the sphericity of the silicon-carbon composite material is 0.5 to 1. A larger sphericity and more regular shape of the silicon-carbon composite material can reduce stress concentration in the negative electrode active layer during volume changes, lower the risk of cracking and breakage of the negative electrode active material, and further improve the cycle life of the lithium-ion secondary battery. Optionally, the sphericity of the silicon-carbon composite material can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, or any value within the range of any two of the above values.

[0073] In some embodiments, the powder compaction density of the silicon-carbon composite material at a pressure of 30,000 N is 0.9 g / cm³. 3 ~1.2g / cm 3 Within this range, the powder compaction density of silicon-carbon composite materials allows for a better balance between improved energy density and cycle life in lithium-ion secondary batteries. Optionally, the powder compaction density of silicon-carbon composite materials at 30,000 N pressure can be 0.9 g / cm³. 3 0.92g / cm 3 0.95g / cm 3 0.98g / cm 3 1g / cm 3 1.02g / cm 3 1.05g / cm 3 1.08g / cm 3 1.1g / cm 3 1.12 g / cm 3 1.15g / cm 3 1.18 g / cm 3 1.2g / cm 3And any value within the range consisting of any two of the above values.

[0074] In some embodiments, the tap density of the silicon-carbon composite material is 0.9 g / cm³. 3 ~1.1g / cm 3 Within this range, the tap density of the silicon-carbon composite material is beneficial for maintaining a relatively stable structure of the negative electrode active layer during battery charging and discharging, thereby improving the battery's cycle life while increasing its energy density. Optionally, the tap density of the silicon-carbon composite material can be 0.9 g / cm³. 3 0.92g / cm 3 0.95g / cm 3 0.98g / cm 3 1g / cm 3 1.02g / cm 3 1.05g / cm 3 1.08g / cm 3 1.1g / cm 3 And any value within the range consisting of any two of the above values.

[0075] In some embodiments, the compacted density of the negative electrode active material powder under a pressure of 30,000 N is 1.25 g / cm³. 3 ~1.8g / cm 3 Optionally, the powder compaction density of the negative electrode active material under a pressure of 30,000 N can be 1.25 g / cm³. 3 1.3g / cm 3 1.35g / cm 3 1.4g / cm 3 1.45g / cm 3 1.5g / cm 3 1.55g / cm 3 1.6g / cm 3 1.65g / cm 3 1.7g / cm 3 1.75g / cm 3 1.8g / cm 3 And any value within the range consisting of any two of the above values.

[0076] In some embodiments, the tap density of the negative electrode active material is 0.95 g / cm³. 3 ~1.25g / cm 3 Optionally, the tap density of the negative electrode active material can be 0.95 g / cm³. 3 0.98g / cm 3 1g / cm 31.02g / cm 3 1.05g / cm 3 1.08g / cm 3 1.1g / cm 3 1.12 g / cm 3 1.15g / cm 3 1.18 g / cm 3 1.2g / cm 3 1.22g / cm 3 1.25g / cm 3 And any value within the range consisting of any two of the above values.

[0077] In some embodiments, the compaction density of the negative electrode active layer is 1.4 g / cm³. 3 ~1.65g / cm 3 The compaction density of the negative electrode active layer is greater than or equal to 1.4 g / cm³. 3 This allows the battery to achieve a higher energy density while maintaining good contact between the negative electrode active materials, which is beneficial for improving the battery's kinetic performance and further enhancing its cycle life. Additionally, the compaction density of the negative electrode active layer is less than or equal to 1.65 g / cm³. 3 The electrolyte can more fully wet the negative electrode active layer, enabling lithium ions to be transported more efficiently within the negative electrode active layer, which is beneficial for improving battery cycle life. Optionally, the compaction density of the negative electrode active layer can be 1.4 g / cm³. 3 1.42g / cm 3 1.45g / cm 3 1.48g / cm 3 1.5g / cm 3 1.52g / cm 3 1.55g / cm 3 1.58g / cm 3 1.6g / cm 3 1.62g / cm 3 1.65g / cm 3 And any value within the range consisting of any two of the above values.

[0078] In this application, the compaction density of the active layer can be tested by the following method: Take an electrode sheet, punch it into a small circular piece with an area of ​​S1, weigh it, and record its weight as M1; measure the thickness of the active layer and record it as T; then wipe off the above-weighed active layer, weigh the current collector, and record it as M0. The compaction density of the active layer PD = (M1 - M0) / (S1 × T).

[0079] In some embodiments, the negative electrode active material of the negative electrode active layer may also include negative electrode active materials known in the art for use in batteries. As a non-limiting example, the negative electrode active material may also include one or more of the following materials: soft carbon, hard carbon, tin-based materials, and lithium titanate, etc. Tin-based materials may include one or more of elemental tin, tin oxides, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0080] Optionally, the negative electrode active material accounts for 91% to 98% of the mass of the negative electrode active layer. For example, the mass percentage of the negative electrode active material in the negative electrode active layer can be 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, or any value within the range of any two of the above values.

[0081] In some embodiments, the negative electrode active layer may optionally include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). Optionally, the binder constitutes 1% to 5% of the negative electrode active layer by mass. Optionally, the binder may constitute 1%, 2%, 3%, 4%, 5%, or any value within the range of any two of the above values.

[0082] In some embodiments, the negative electrode active layer may optionally include a conductive agent. The conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. Optionally, the conductive agent accounts for 0.2% to 2% of the mass percentage of the negative electrode active layer. Optionally, the conductive agent accounts for 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, or any value within the range of any two of the above values.

[0083] In some embodiments, the negative electrode active layer may optionally include other additives, such as a thickener. The thickener may be sodium carboxymethyl cellulose (CMC-Na). Optionally, the thickener accounts for 0.8% to 2% of the mass of the negative electrode active layer. Optionally, the mass percentage of the thickener in the negative electrode active layer may be 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, or any value within the range of any two of the above values.

[0084] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be obtained by forming a metal material on the polymer material substrate. Non-limiting examples of the metal material in the negative electrode current collector may include one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. Non-limiting examples of the polymer material substrate in the negative electrode current collector may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0085] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder, and any other components, in a solvent to form a negative electrode slurry. Optionally, a non-limiting example of a solvent is deionized water. The negative electrode slurry is coated onto at least one surface of the negative electrode current collector, and after processes such as drying and cold pressing, the negative electrode sheet is obtained. The surface of the negative electrode current collector coated with the negative electrode slurry can be a single surface of the negative electrode current collector or both surfaces of the negative electrode current collector.

[0086] It is understood that a lithium-ion secondary battery includes a positive electrode. The positive electrode includes a positive current collector and a positive active layer located on at least one surface of the positive current collector. The positive active layer contains a positive active material.

[0087] In some embodiments, the positive electrode active material may be a known positive electrode active material for batteries. As a non-limiting example, the positive electrode active material may include one or more of the following materials: lithium-containing phosphates with an olivine structure, lithium-containing transition metal oxides, and their respective modified compounds.

[0088] In some embodiments, lithium-containing phosphates may include at least one of lithium iron phosphate, a composite of lithium iron phosphate and carbon, lithium manganese iron phosphate, and a composite of lithium manganese iron phosphate and carbon. Lithium-containing phosphates may also include one or more of lithium manganese phosphate and a composite of lithium manganese phosphate and carbon.

[0089] Optionally, the lithium phosphate with olivine structure accounts for 50% to 100% of the mass of the positive electrode active material. For example, the lithium phosphate with olivine structure accounts for 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100% of the mass of the positive electrode active material, as well as any value within the range of any two of the above values.

[0090] Optionally, the lithium phosphate with olivine structure accounts for 95% to 98.5% of the mass percentage of the positive electrode active layer. For example, the lithium phosphate with olivine structure accounts for 95%, 96%, 97%, 98%, 98.5% of the mass percentage of the positive electrode active layer, as well as any value within the range of any two of the above values.

[0091] In some embodiments, the positive electrode active material includes Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y A lithium-containing transition metal oxide, wherein 0.2≤x≤1.2, 0.2≤a≤1, 0≤b≤1, 0≤c≤1, a+b+c=1, 0≤d<1, 0≤y<2, M includes one or more of Zr, Sr, B, Sn, Al, Mg, Fe, Cu, V, Ti, Zr, W, Sb, Dy, and Te, and A includes one or more of N, P, S, and halogen elements. The chemical formula is Li. x (Ni a Co b Mn c ) 1-d M d O 2-y A y Lithium-containing transition metal oxides have high specific capacity, which can further improve the energy density of lithium-ion secondary batteries.

[0092] Understandably, 'a' is typically used to represent the nickel content in lithium-containing transition metal oxides. A larger 'a' indicates a higher nickel content, while a smaller 'a' indicates a lower nickel content. As some possible examples of 'a', 'a' can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, or any value within the range of any two of the above values.

[0093] Understandably, 'b' is typically used to represent the cobalt content in lithium-containing transition metal oxides. A larger 'b' indicates a higher cobalt content, while a smaller 'b' indicates a lower cobalt content. As some possible examples of 'b', it can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, and any value within the range of any two of the above values.

[0094] Understandably, 'c' is typically used to represent the manganese content in lithium-containing transition metal oxides. A larger 'c' indicates a higher manganese content, while a smaller 'c' indicates a lower manganese content. As some possible examples of 'c', it can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, and any value within the range of any two of the above values.

[0095] Understandably, d is typically used to represent the content of element M in lithium-containing transition metal oxides. A larger d indicates a higher content of element M, while a smaller d indicates a lower content of element M. As some possible examples of d, d can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, and any value within the range of any two of the above values. Optionally, 0 ≤ d ≤ 0.05.

[0096] Understandably, x is typically used to represent the lithium content in lithium-containing transition metal oxides. A larger x indicates a higher lithium content, while a smaller x indicates a lower lithium content. As some possible examples of x, x can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, and any value within the range of any two of the above values.

[0097] Understandably, y is typically used to represent the content of element A in lithium-containing transition metal oxides. A larger y indicates a higher content of element A, while a smaller y indicates a lower content of element A. As some possible examples of y, y can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 1.91, 1.92, 1.93, 1.94, 1.95, 1.96, 1.97, 1.98, 1.99, and any value within the range of any two of the above values. Optionally, 0 ≤ y ≤ 0.05.

[0098] It is understandable that A includes one or more of N, P, S and halogen elements, where halogen elements can be F, Cl, Br, etc.

[0099] Optionally, the lithium-containing transition metal oxide includes LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.5 Co 0.25 Mn 0.25 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.9 Co 0.09 Mn 0.01 O2, LiNi 0.92 Co 0.05 Mn 0.03 O2, LiNi 0.96 Co 0.02 Mn 0.02 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, etc.

[0100] Optionally, the chemical formula is Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y The lithium-containing transition metal oxide accounts for 90% to 100% of the mass of the positive electrode active material. For example, the chemical formula Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y The percentage of lithium-containing transition metal oxides in the positive electrode active material by mass is 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, or any value within the range of any two of the above values.

[0101] Optionally, the chemical formula is Li x (Ni aCo b Mn c ) 1-d M d O 2-y A y The lithium-containing transition metal oxide accounts for 95% to 98.5% of the mass percentage of the positive electrode active layer. For example, the chemical formula Li x (Ni a Co b Mn c ) 1-d M d O 2-y A y The lithium-containing transition metal oxide accounts for 95%, 96%, 97%, 98%, 98.5% of the mass of the positive electrode active layer, as well as any value within the range of any two of the above values.

[0102] In some embodiments, the positive electrode active material may further include one or more of the following materials: lithium cobalt oxide, lithium manganese oxide, lithium manganese cobalt oxide, and modified compounds thereof. Non-limiting examples of lithium cobalt oxide may include LiCoO2. Non-limiting examples of lithium manganese oxide may include LiMnO2, LiMn2O4, etc.

[0103] In some embodiments, the positive electrode active layer may optionally include a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins. Optionally, the binder accounts for 0.7% to 3% of the mass percentage of the positive electrode active layer. For example, the binder percentage of the positive electrode active layer may be 0.7%, 0.9%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, or any value within the range of any two of the above values.

[0104] In some embodiments, the positive electrode active layer may optionally include a conductive agent. As a non-limiting example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. Optionally, the conductive agent accounts for 0.8% to 2% of the mass percentage of the positive electrode active layer. For example, the mass percentage of the conductive agent in the positive electrode active layer may be 0.8%, 0.9%, 1%, 1.2%, 1.5%, 1.8%, 2%, or any value within the range of any two of the above values.

[0105] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be obtained by forming a metal material on a polymer material substrate. Non-limiting examples of the metal material in the positive electrode current collector may include one or more of aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. Non-limiting examples of the polymer material substrate in the positive electrode current collector may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0106] In some embodiments, the positive electrode sheet can be prepared by dispersing the components used to prepare the positive electrode sheet, such as the positive electrode active material, conductive agent, binder, and any other components, in a solvent to form a positive electrode slurry; coating the positive electrode slurry onto at least one surface of the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing, and other processes. The solvent can be selected from, but is not limited to, any of the solvents described in the foregoing embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode current collector coated with the positive electrode slurry can be a single surface of the positive electrode current collector or both surfaces of the positive electrode current collector.

[0107] In some embodiments, the lithium-ion secondary battery also includes an electrolyte. The electrolyte serves to conduct ions between the positive and negative electrode plates. This application does not impose any particular limitation on the type of electrolyte, which can be selected according to requirements. For example, the electrolyte can be liquid, gel, or all-solid.

[0108] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0109] In some embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonylimide (LiFSI), lithium bistrifluoromethanesulfonylimide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).

[0110] In some embodiments, the solvent may include one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butenyl carbonate, fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0111] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.

[0112] In some embodiments, the additives in the electrolyte may include, but are not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethyl ethylene carbonate (TFPC).

[0113] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0114] In some embodiments, the lithium-ion secondary battery may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.

[0115] In some embodiments, the outer packaging of the lithium-ion secondary battery can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the lithium-ion secondary battery can also be a soft pack, such as a pouch. The soft pack can be made of plastic; further, non-limiting examples of plastic may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0116] This application does not impose any particular limitation on the shape of the lithium-ion secondary battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 This is an example of a square-structured lithium-ion secondary battery 1.

[0117] In some implementations, refer to Figure 2 The outer packaging may include a housing 11 and a cover plate 13. The housing 11 may include a bottom plate and side plates connected to the bottom plate, the bottom plate and side plates forming a receiving cavity. The housing 11 has an opening communicating with the receiving cavity, and the cover plate 13 can be placed over the opening to close the receiving cavity. The positive electrode, negative electrode, and separator can be formed into an electrode assembly 12 by a winding process or a stacking process. The electrode assembly 12 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 12. The lithium-ion secondary battery 1 may contain one or more electrode assemblies 12, which can be selected by those skilled in the art according to actual needs.

[0118] In some implementations, the lithium-ion secondary battery can be a single battery cell, a battery module, or a battery pack.

[0119] The battery module includes at least one lithium-ion secondary battery. The battery module may contain one or more lithium-ion secondary batteries, and those skilled in the art can select an appropriate number based on the application and capacity of the battery module.

[0120] In a battery module, multiple lithium-ion secondary batteries can be arranged sequentially along the length of the module. Of course, they can also be arranged in any other manner. Furthermore, these multiple lithium-ion secondary batteries can be secured using fasteners.

[0121] Optionally, the battery module may also include a housing with a receiving space in which multiple lithium-ion secondary batteries are housed.

[0122] In some embodiments, the battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more. Those skilled in the art can select an appropriate number according to the application and capacity of the battery pack.

[0123] The battery pack may include a battery box and multiple battery modules disposed within the battery box. The battery box includes an upper body and a lower body, with the upper body covering the lower body to form a closed space for accommodating the battery modules. The multiple battery modules can be arranged in any manner within the battery box.

[0124] In addition, this application also provides an electrical device, which includes the lithium-ion secondary battery provided in this application. The battery can be used as a power source for the electrical device or as an energy storage unit of the electrical device. The electrical device may include, but is not limited to, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Among them, mobile devices may be, for example, mobile phones, laptops, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to.

[0125] As an electrical device, lithium-ion rechargeable batteries can be selected according to its usage requirements.

[0126] Figure 3 Here is an example of an electrical device 2. This electrical device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of this electrical device, a battery pack or battery module can be used.

[0127] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can be powered by a battery.

[0128] To make the technical problems, technical solutions, and beneficial effects solved by this application clearer, the application will be further described in detail below with reference to embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit this application or its applications. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0129] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0130] Example 1

[0131] (1) Positive electrode plate

[0132] LiNi, the positive electrode active material 0.8 Co0.1 Mn 0.1 O2, polyvinylidene fluoride binder, and super P conductive agent are mixed in a weight ratio of 96:2:2, and N-methylpyrrolidone solvent is added and stirred to prepare a positive electrode slurry. The positive electrode slurry is then coated onto a current collector aluminum foil, dried, and subjected to cold pressing, slitting, and cutting to form a positive electrode sheet.

[0133] (2) Negative electrode plate

[0134] Artificial graphite, silicon-carbon composite material, conductive agent carbon black, thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were mixed in a weight ratio of 76:19:1.5:1:2.5, and then added to deionized water as a solvent. The mixture was stirred to prepare a negative electrode slurry. The negative electrode slurry was then coated onto a current collector copper foil, dried, and subjected to cold pressing, slitting, and cutting to form the negative electrode sheet. The silicon-carbon composite material had an average particle size of 8 μm, a sphericity of 0.6, and a powder compaction density of 1.02 g / cm³ under 30,000 N pressure. 3 The tap density of the silicon-carbon composite material is 1 g / cm³. 3 Artificial graphite consists of single-crystal particles with an average particle size of 6 μm, a sphericity of 0.75, and a compacted density of 1.65 g / cm³ under 30,000 N pressure. 3 The tap density of artificial graphite is 1.2 g / cm³. 3 The compacted density of the negative electrode active material powder under 30,000 N pressure is 1.55 g / cm³. 3 The tap density of the negative electrode active material is 1.15 g / cm³. 3 The compaction density of the negative electrode active layer is 1.6 g / cm³. 3 .

[0135] (3) Separating membrane

[0136] Polyethylene (PE) film is used as the separator.

[0137] (4) Electrolyte

[0138] In an argon-atmospheric glove box with a water content of <10 ppm, diethyl carbonate (DEC), methyl ethyl carbonate (EMC), and ethylene carbonate (EC) were mixed in a weight ratio of 1:1:1 to obtain an organic solvent. LiPF6 was then dissolved in the organic solvent at a concentration of 1.0 mol / L, followed by the addition of fluoroethylene carbonate (FEC), with the FEC content being 8% of the total electrolyte mass.

[0139] (5) Lithium-ion secondary battery

[0140] The positive electrode, separator, and negative electrode are prepared in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The electrodes are then wound to obtain a bare cell, and tabs are welded on. The bare cell is placed in an outer packaging shell, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, and shaping, a lithium-ion secondary battery is obtained.

[0141] Examples 2-10 and Comparative Examples 1-4 were manufactured using a similar preparation method to Example 1. Specific design information is shown in Table 1.

[0142] Comparative Example 5

[0143] Compared to Example 1, Comparative Example 5 differs in that the silicon-carbon composite material is replaced with an equal mass of silicon-oxygen material. The silicon-oxygen material has similar average particle size, sphericity, powder compaction density, and tap density to the silicon-carbon composite material in Example 1.

[0144] Test case

[0145] (1) The lithium-ion secondary batteries of Example 2 and Comparative Example 1 were fully discharged, and the negative electrode sheets obtained after disassembly were observed. The cross-section of the negative electrode sheets along the thickness direction was observed. The results are as follows: Figure 4 As shown. Figure 4 In the diagram, gray particles represent graphite, white particles represent silicon-carbon composite materials, (a) represents Example 2, and (b) represents Comparative Example 1. Figure 4 It can be seen that the uniformity of the mixing of silicon-carbon composite material and graphite in the negative electrode active layer corresponding to (a) is higher than that in (b), indicating that by matching the average particle size of silicon-carbon composite material and artificial graphite, a foundation can be laid for improving the pore distribution of the negative electrode active layer.

[0146] (2) The cross-sections of the negative electrode sheets in Example 2 and Comparative Example 1 in (1) were analyzed using Avizo software. The results are as follows: Figure 5 As shown. Figure 5 In the diagram, gray particles represent graphite, white particles represent silicon-carbon composite materials, and the yellow area represents the porosity distribution in the negative electrode sheet. (a) represents Example 2, and (b) represents Comparative Example 1. Figure 5 It can be seen that the uniformity of pore distribution in the negative electrode active layer corresponding to (a) is higher than that in (b), indicating that the pore distribution of the negative electrode active layer can be improved by matching the average particle size of silicon-carbon composite materials and artificial graphite. This is understandable. Figure 5 and Figure 4 The selection of cross-sections differs, resulting in slight variations in the distribution of silicon-carbon composite materials and graphite in the images.

[0147] (3) The cycle life of the lithium-ion secondary batteries in the examples and comparative examples was tested. The test method was as follows: the battery was charged at 0.33C to 4.25V at 25℃, then charged at a constant voltage to 0.05C, and after standing for 30 minutes, it was discharged at a constant current of 0.33C to 2.5V. This constituted one cycle of charge and discharge. The discharge capacity at this time was recorded as the initial capacity C0. Then the battery was cycled and discharged, and the discharge capacity after each cycle was recorded until the discharge capacity of the battery decreased to 80% of the initial discharge capacity. The number of cycles at this time was used to characterize the cycle life of the battery. The cycle life results are shown in Table 1.

[0148] (4) The rate performance of the lithium-ion secondary batteries of Example 2 and Comparative Example 1 was tested. The test method was as follows: the battery was charged to 4.25V at 0.33C at 25°C, charged to 0.05C at constant voltage, left to stand for 30 minutes, and then discharged to 2.5V at a constant current of 0.33C. The discharge capacity at this time was recorded as the initial capacity C0. The battery was sequentially charged at constant current rates of 0.5C0, 1.0C0, 1.5C0, 2.0C0, 2.5C0, and 3.0C0 to either 4.25V or 0V negative electrode cutoff potential, whichever came first. After each charge, it was discharged at 1C0 to 2.5V. The negative electrode potential corresponding to the state of charge (SOC) at different rates was recorded at 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, and 80%. The charge rate-negative electrode potential curves at different SOC states were plotted. After linear fitting, the charge rate corresponding to a negative electrode potential of 0V at different SOC states was obtained. The results are shown below. Figure 6 As shown. By Figure 6 As can be seen, the lithium-ion secondary battery corresponding to Example 2 has a higher rate performance compared to Comparative Example 1. This indicates that by combining silicon-carbon composite materials and artificial graphite with varying average particle sizes, the rate performance of the battery can be improved, thereby enhancing its fast-charging performance.

[0149] The charging time T, in minutes, is calculated using the formula (60 / C10%SOC+60 / C15%SOC+60 / C20%SOC+60 / C25%SOC+60 / C30%SOC+60 / C35%SOC+60 / C40%SOC+60 / C45%SOC+60 / C50%SOC+60 / C55%SOC+60 / C60%SOC+60 / C65%SOC+60 / C70%SOC+60 / C75%SOC+60 / C80%SOC) × 5%. Here, "C10%SOC", "C15%SOC", ..., "C80%SOC" represent the corresponding charging rates for each state of charge. For example, "C10%SOC" represents the charging rate at a 10% SOC state of charge. A shorter charging time T indicates better fast-charging performance of the battery. The charging times of the batteries in each embodiment and comparative example are shown in Table 1, obtained through calculation.

[0150] Table 1

[0151]

[0152] In Table 1, the average particle size is expressed in μm. The powder compaction density represents the compaction density of the material under a pressure of 30,000 N, and is expressed in g / cm³. 3 The unit of tap density is g / cm³. 3 The average particle size ratio represents the ratio of the average particle size of the silicon-carbon composite material to the average particle size of graphite. In the cycle life data, portions with fewer than 10 cycles are rounded to the nearest tens digit, therefore the units digit in the cycle life data is always 0.

[0153] As can be seen from the comparison between Examples 1-10 and Comparative Examples 1-4, using appropriate average particle size and average particle size ratio of silicon-carbon composite materials and graphite can enable batteries to achieve both good cycle performance and charging performance.

[0154] As can be seen from the comparison between Examples 1 and Examples 7-8, the sphericity of graphite within a suitable range is beneficial for the battery to better balance good cycle performance and charging performance.

[0155] As can be seen from the comparison between Examples 1 and Examples 9-10, the sphericity of silicon-carbon composite materials within a suitable range is beneficial for the battery to better balance good cycle performance and charging performance.

[0156] As can be seen from Example 1 and Comparative Example 5, when the negative electrode active layer of the battery includes silicon-carbon composite material and graphite, the battery can have better cycle performance and better charging performance.

[0157] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0158] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A lithium-ion secondary battery, characterized in that, The device includes a negative electrode sheet, which comprises a negative current collector and a negative active layer located on at least one surface of the negative current collector. The negative active material of the negative active layer comprises a silicon-carbon composite material and graphite. The average particle size of the silicon-carbon composite material is less than or equal to 10 μm, and the ratio of the average particle size of the silicon-carbon composite material to the average particle size of the graphite is 0.8 to 1.

2. The silicon-carbon composite material comprises a porous carbon substrate having a pore structure, and silicon-containing materials are distributed within the pore structure.

2. The lithium-ion secondary battery according to claim 1, characterized in that, The silicon-carbon composite material and the graphite are mixed together.

3. The lithium-ion secondary battery according to any one of claims 1 to 2, characterized in that, The average particle size of the silicon-carbon composite material is greater than or equal to 7 μm.

4. The lithium-ion secondary battery according to any one of claims 1 to 3, characterized in that, The average particle size of the graphite is 6μm to 12μm.

5. The lithium-ion secondary battery according to any one of claims 1 to 4, characterized in that, The sphericity of the graphite is 0.5 to 1.

6. The lithium-ion secondary battery according to any one of claims 1 to 5, characterized in that, The graphite includes artificial graphite with a single-particle morphology.

7. The lithium-ion secondary battery according to any one of claims 1 to 6, characterized in that, The compacted density of the graphite powder under 30,000 N pressure is 1.6 g / cm³. 3 ~1.8g / cm 3 .

8. The lithium-ion secondary battery according to any one of claims 1 to 7, characterized in that, The tap density of the graphite is 1.05 g / cm³. 3 ~1.25g / cm 3 .

9. The lithium-ion secondary battery according to any one of claims 1 to 8, characterized in that, The sphericity of the silicon-carbon composite material is 0.5~1.

10. The lithium-ion secondary battery according to any one of claims 1 to 9, characterized in that, The silicon-carbon composite material has a powder compaction density of 0.9 g / cm³ under a pressure of 30,000 N. 3 ~1.2g / cm 3 .

11. The lithium-ion secondary battery according to any one of claims 1 to 10, characterized in that, The tap density of the silicon-carbon composite material is 0.9 g / cm³. 3 ~1.1g / cm 3 .

12. The lithium-ion secondary battery according to any one of claims 1 to 11, characterized in that, The silicon-containing material includes elemental silicon and lithium silicate located on the surface of the elemental silicon.

13. The lithium-ion secondary battery according to any one of claims 1 to 12, characterized in that, The silicon-carbon composite material accounts for 1% to 50% of the mass of the negative electrode active material; optionally, the silicon-carbon composite material accounts for 5% to 30% of the mass of the negative electrode active material.

14. The lithium-ion secondary battery according to any one of claims 1 to 13, characterized in that, The silicon-carbon composite material accounts for 0.9% to 49% of the mass of the negative electrode active layer.

15. The lithium-ion secondary battery according to any one of claims 1 to 14, characterized in that, The graphite accounts for 50% to 99% of the mass of the negative electrode active material; optionally, the graphite accounts for 70% to 95% of the mass of the negative electrode active material.

16. The lithium-ion secondary battery according to any one of claims 1 to 15, characterized in that, The compacted density of the negative electrode active material under a pressure of 30,000 N is 1.25 g / cm³. 3 ~1.8g / cm 3 .

17. The lithium-ion secondary battery according to any one of claims 1 to 16, characterized in that, The tap density of the negative electrode active material is 0.95 g / cm³. 3 ~1.25g / cm 3 .

18. The lithium-ion secondary battery according to any one of claims 1 to 17, characterized in that, The compaction density of the negative electrode active layer is 1.4 g / cm³. 3 ~1.65g / cm 3 .

19. An electrical appliance, characterized in that, The lithium-ion secondary battery includes any one of claims 1 to 18.